2010
DOI: 10.1111/j.1365-2265.2010.03846.x
|View full text |Cite
|
Sign up to set email alerts
|

High thyrotrophin levels at end term increase the risk of breech presentation

Abstract: Summary Objective  To study the relationship between maternal thyrotrophin (TSH) and breech presentation at term. Design  Combined data sets of two prospective studies to obtain adequate epidemiological power. Patients   One thousand and fifty‐eight healthy pregnant women (58 breech, 1000 cephalic) and 131 women who presented in breech at an obstetrical outpatient clinic. Measurements  Maternal thyroid parameters [TSH, free thyroid hormone (FT4), thyroid peroxidase antibody (TPO‐Ab)] and foetal presentation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
(48 reference statements)
0
11
1
Order By: Relevance
“…1 There were no differences in any of the baseline demographics of both groups in our study unlike the previous study where there were a significantly higher number of primiparous mothers in the breech group. 2 While having a similar rate of successful ECV to the previous study 3 (55 vs 54%), we were unable to confirm their findings of higher TSH concentrations increasing the risk of ECV failure; however, they did have a significantly higher number of primiparous mothers in their cohort than our study (66% vs 44%, P < 0Á001) which may have impacted on their results.…”
Section: Variables In Pregnancycontrasting
confidence: 72%
See 1 more Smart Citation
“…1 There were no differences in any of the baseline demographics of both groups in our study unlike the previous study where there were a significantly higher number of primiparous mothers in the breech group. 2 While having a similar rate of successful ECV to the previous study 3 (55 vs 54%), we were unable to confirm their findings of higher TSH concentrations increasing the risk of ECV failure; however, they did have a significantly higher number of primiparous mothers in their cohort than our study (66% vs 44%, P < 0Á001) which may have impacted on their results.…”
Section: Variables In Pregnancycontrasting
confidence: 72%
“…This is in contrast to the previous studies from the Netherlands. 1,2 There may be several reasons for the discrepancy in results: in the United Kingdom, a breech presentation identified from 36 weeks onward is considered to be an abnormal position and is actively monitored by community midwives to enable the opportunity for ECV. Our cohorts were identified prospectively during routine clinical practice resulting in a large number of breech presentations all of whom were able to be included in the final analysis irrespective of presentation at the time of delivery; women with breech presentation who had successful ECV were excluded in the previous study.…”
Section: Variables In Pregnancymentioning
confidence: 98%
“…In contrast, a prospective study of 10,990 women in US and Ireland with biochemical evidence of SH did not reveal excessive adverse pregnancy outcomes [ 45 ]. Recent studies from The Netherlands documented an association between TSH levels exceeding >2.4 mIU/mL between the 35th and 38th week of gestation are associated with the approximately 2-fold increased risk for breech presentation [ 46 , 47 ]. Elevated TSH levels earlier during the pregnancy were not associated with risk of breech presentation.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our research group showed that at 36 weeks gestation women with TSH levels above 2.5 mIU/l are at risk for breech presentation [ 8 , 9 ]. It is stated that fetal movements and mobility are a prerequisite for spontaneous version into the cephalic position [ 10 ].…”
Section: Introductionmentioning
confidence: 99%